Saintific Approach on Islamic Religious Education Curriculum in The Perspective of Al-Qur’an - Muhammad Hambal (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
The purpose of this study is to find out how to conceptualize scientific approaches on Islamic education curriculum, and how to analyze the scientific approach in Islamic religious education curriculum in the perspective of the Qur'an. This study used the library research method, while the data collection method used the documentation method. In data analysis or processing, the author used thematic methods. The results of this study are the concept of a scientific approach consisting of five activities including observing, asking, exploring/trying, reasoning/associating, and communicating which in relation to the perspective of Qur’an is that the five processes are demands for humans to be able to observe everything around them that is also a science, and should ask everything that has not been understood to the experts, then be able to practice or try to understand what has been received and used reason as best as possible so that there are no unfavorable perceptions that have no basis or just to conclude without any consideration of how it can strengthen that knowledge, then in the process of communicating we should be able to convey a knowledge that we have understood to others who do not understand it as in the verse, and overall it also demands in order to be able to think intellectually. Keywords: Scientific, Curriculum and Islamic Religious Education